Ridge-furrow mulching with black plastic film improves maize yield more than white plastic film in dry areas with adequate accumulated temperature - Qin, Xiaoliang; Li, Yüze; Han, Yunliang; Hu, Yingchun; Li, Yajun; Wen, Xiaoxia; Liao, Yuncheng; Siddique, Kadambot H.M. (Agricultural and forest meteorology, 2018)
•BP treatment produced lower topsoil temperatures than WP treatment.•Maize had a longer growth period under BP than WP treatment.•BP produced less total weed biomass at harvest than WP or conventional planting.•BP treatment produced higher grain yields than WP treatment.•BP was more net income than WP when temperature did not limit crop growth. Ridge-furrow (RF) farming systems with white plastic film have been used extensively for maize (Zea mays L.) production in semiarid areas, yet black plastic film has less effect on soil temperature than white plastic film. This study examined whether RF systems with black plastic film perform better than white film in rainfed areas with adequate accumulated temperature. In 2016 and 2017, a field experiment was conducted in the Loess Plateau of China that involved sowing maize under three farming systems: conventional flat planting (CK), ridge-furrow (RF) system with white plastic (WP), and RF with black plastic (BP). The growth period for maize under BP was 5 days longer than under WP and 5 days shorter than CK in two years. The BP treatment produced a significantly higher leaf area index in maize than the CK and WP treatments at 100 and 120 days after sowing (DAS) in two years. Topsoil temperatures in the BP treatment were significantly lower than WP at 20, 80 and 100 DAS in two years. The BP treatment had better soil water content and soil water storage than WP during growth in two years. The BP and WP treatments had similar water use efficiencies, which were 44.98% averaged higher than the CK treatment in two years. The BP treatment produced 11.79% averaged more grain yield than the WP treatment in two years; both treatments produced more grain yield than the CK treatment. The BP treatment produced 55.18% averaged less total weed biomass than the other two treatments at harvest in two years. Net income in the BP treatment was 13.52% averaged higher than the WP treatment, and 18% averaged higher when sprayed. RF with black plastic film can be adopted in maize crops sown in rainfed, arid areas where temperature does not limit crop growth.